2005
DOI: 10.1081/jas-200054633
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Use and Quality of Life Among Patients with Asthma and Panic Disorder

Abstract: The purpose of this study was to assess the associations between panic disorder (PD) and health services use, health-related quality of life, and use of short-acting β 2 -agonists among individuals with asthma. We studied 21 adults with comorbid asthma and panic disorder (asthma-PD) and 27 asthma patients without PD (asthma-only). Participants attended a single session at a laboratory to complete the study. A retrospective chart review was conducted to assess use of health care resources for asthma treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
1
24
1
3
Order By: Relevance
“…They carry a negative prognostic value and are associated with worse health outcomes for people with asthma, including: poor medication adherence [11]; poor health-related quality of life [37], increased use of both scheduled and urgent healthcare [12,38,39]. Current NICE guidelines recommend the active treatment of depression in patients with long term conditions, beginning with nonpharmacological approaches but also including antidepressants if indicated [40].…”
Section: Discussionmentioning
confidence: 99%
“…They carry a negative prognostic value and are associated with worse health outcomes for people with asthma, including: poor medication adherence [11]; poor health-related quality of life [37], increased use of both scheduled and urgent healthcare [12,38,39]. Current NICE guidelines recommend the active treatment of depression in patients with long term conditions, beginning with nonpharmacological approaches but also including antidepressants if indicated [40].…”
Section: Discussionmentioning
confidence: 99%
“…1). Sixty-five primary studies (69 publications) fulfilled inclusion criteria (diabetes: n = 23 [10,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56]; CAD: n = 26 [57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83]; asthma: n = 13 [84,85,86,87,88,89,90,91,92,93,94,95,96,97]; chronic back pain: n = 3 [98,99,100]; colorectal cancer: n = 0). In most cases, depressive disorders were studied (n = 45), followed by anxiety disorders (n = 14), any mental disorder (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, this might lead to an increased use of health care resources to find relieve from the overly negatively perceived symptom. Previous reports have indeed demonstrated that particularly those dyspneic patient groups with a comorbid depression or anxiety disorder show an overuse of β 2 -agonists [28, 29], more visits to their physician [29] and higher rehospitalization rates [30] compared to patients not suffering from these comorbidities. Regression analyses carried out by Main et al [27] have previously underlined this relationship by showing that negative affectivity of asthma patients predicts the use of reliever medications, a relationship which might be mediated by accurate symptom perception.…”
Section: Discussionmentioning
confidence: 99%
“…This dimension itself might be highly impacted upon by negative affectivity of patients (e.g., depression and anxiety), which is frequent in obstructive pulmonary disorders [21,22,23] and might be associated with inaccurate perception of dyspnea [24,25,26], inadequate use of medication [27, 28], frequent visits to the physician [29] and high rehospitalization rates [30]. However, it is entirely unknown how sensory and affective aspects of dyspnea influence the Borg scale’s measurement of dyspnea, which does not differentiate between these distinct aspects.…”
Section: Introductionmentioning
confidence: 99%